Analgesic, Anti-Inflammatory, and GC-MS Studies on Castanospermum australe A. Cunn. & C. Fraser ex Hook. - Thankarajan Sajeesh; Thangaraj Parimelazhagan (The Scientific World Journal)
The present study was aimed to evaluate the analgesic and anti-inflammatory properties of Castanospermum australe and to profile phytochemicals by GC-MS. The ethanolic extracts were prepared by successive solvent extraction using Soxhlet apparatus. The analgesic activity was analyzed by hot plate method and acetic acid-induced writhing test whereas anti-inflammatory study was done by carrageenan induced paw oedema model. The acute toxicity study revealed that ethanol extracts of leaf and bark of C. australe were safe even at a higher dose of 2000 mg/kg whereas ethanol extract of seed was toxic at the same dose. In both hot plate method (5.85 s) and acetic acid-induced writhing test (57%), the leaf ethanol extract exhibited significant analgesic activity (P<0.001) at a dose of 400 mg/kg. The anti-inflammatory activity of leaf extract was exhibited by the reduction in paw linear diameter by 64.76% at 400 mg/kg in carrageenan induced paw oedema. The GC-MS analysis of the ethanol extract of leaf revealed sixteen major compounds of which 1,7-dimethyl-4,10-dioxa-1,7-diazacyclododecane, (+)-N-methylephedrine, and permethylspermine were found to be pharmaceutically and the most important. These findings justify that C. australe can be a valuable natural analgesic and anti-inflammatory source which seemed to provide potential phytotherapeutics against various ailments.